Robust control of sampled-data system subject to input time-delay - Wang, Shigang; Bi, Yongli; Bi, Jun; Wang, Xueliang; Qi, Wenjuan; Cong, Shen; Sheng, Zunbing (Chinese Control Conference, 2016)
This paper investigates robust control for a class of sampled-data system with long time-delay. The control input is subject to long time-delay, and the state includes norm-bounded perturbation, which roots in the process of model establishing. Moreover, the direct distribution method of long time-delay is adopted to design robust controller which ensures robust stability and satisfies a preset performance index for sampled-data system. The proposed stability condition is given in the light of LMI, an illustrative numerical example is provided to show effectiveness and feasibility.